MICROBIAL BIOTRANSFORMATION OF (R)-(+)- LIMONENE BY Penicillium digitatum DSM 62840 FOR PRODUCING (R)-(+)-TERPINEOL - PRIETO V., Gloria A.; PEREA, Janeth A.; ORTIZ L., Claudia C. (Vitae, 2011)
Microbial biotransformation is a relevant strategy to obtain high added value natural compounds undercontrolled environmentally friendly conditions. In this research work, the biotransformation of (R)-(+)-limonene using Penicillium digitatum DSM 62840 was evaluated. The study variables were the following:culture medium, pH, microorganism growth phase, substrate concentration, and inducing effect of thesubstrate. The results showed that a concentration of 14.7 mM limonene in the medium named maltyeast broth at a pH of 3.5, inoculated with induced spores at the early stage of the exponential growth,produces a high specificity and the highest concentration (1864 mg/L) of (R)-(+)-α-terpineol. Theproduct obtained has a considerable potential industrial application.